Low-temperature crystallization of poly(butylene succinate). (September 2017) - Di Lorenzo, Maria Laura; Androsch, René; Righetti, Maria Cristina
Graphical abstract: Highlights: Sub-Tg crystallization of semicrystalline PBS is proven by TMDSC. PBS crystals grown in the glass, melt and recrystallize at Tg. Crystallization of PBS below Tg possibly involves part of the RAF. Abstract: Low-temperature crystallization of poly(butylene succinate) (PBS) was investigated by conventional and temperature-modulated differential scanning calorimetry (DSC and TMDSC). After completion of primary crystallization, cooling of semicrystalline PBS to temperatures near or even below the glass transition temperature ( T g ) leads to additional crystal growth. Such crystallization below T g is identified by detection of frequency- and time-dependent reversing heat-capacity in non-isothermal and quasi-isothermal TMDSC analyses, respectively. Moreover, crystallization in the glassy state causes a shift of T g to higher temperatures, thus affecting the properties of the amorphous phase. Low-temperature crystallization of amorphous PBS was recently reported in the literature and linked to completion of enthalpy relaxation of the PBS glass. In the present study, low-temperature crystallization has been shown to occur also in semicrystalline PBS, with low temperature crystallization probably involving constrained amorphous segments already coupled with the crystals.